Police officers who are physically active and have low levels of body fat show better reaction time - Crocetta T.B.* (2018)
Copyright © 2017 American College of Occupational and Environmental Medicine.Objective: To analyze the relationship between reaction time (RT), level of physical activity (PA), and anthropometric indicators in police officers in Special Operation Units. Methods: Twenty-two police officers (34.5±9.1 years old) from Santa Catarina, Brazil, who were members of a Special Operation Coordination Unit. RT was measured by the Vienna Test System. Were obtained values of body mass index (BMI), body fat (BF), and waist-tohip ratio. PA was investigated using the Physical Activity Evaluation Questionnaire. Results: Younger police officers (less than 34 years) and BF less than 15% presented better performance in RT when compared with older, and BF more than 15%, respectively. RT was negatively related to PA (rho=-0.48, P<0.05), and positively related to BF (rho=0.76, P<0.01) and to BMI (rho=0.46, P<0.05). Conclusions: Participants from the group with greater BF and insufficient PA reacted significantly slower than others.